Jihad Beyond Islam - Marranci, Gabriele (Berg Publishers, 2006)
'Jihad' is a highly charged word. Often mistranslated as 'Holy War', it has become synonymous with terrorism. Current political events have entirely failed to take account of the subtlety and complexity of jihad. Like many concepts with a long history, different cultural ideas have influenced the religious aspects of jihad. As a result its original meaning has been adapted, modified and destabilized - never more than at the present time. How does jihad manifest itself in Muslims' everyday lives? What impact has 9/11 and its backlash had on jihad? By observing the current crisis of identity among ordinary Muslims, this timely book explores why, and in what circumstances Muslims speak of jihad. In the end, jihad is what Muslims say it is. Marranci offers us a nuanced and sophisticated anthropological understanding of Muslims' lives far beyond the predictable cliches. Have a look at the author´s blog hereExplores the different cultural ideas that have influenced the religious aspects of jihad. 'jihad', a term often mistranslated as 'Holy War', has become synonymous with terrorism. This book, by observing the crisis of identity among ordinary Muslims, explores why, and in what circumstances Muslims speak of jihad.Gabriele Marranci is Lecturer in the Anthropology of Religion, School of Divinity and Religious Studies, University of Aberdeen. He is the founding editor of Contemporary Islam: Dynamics of Muslim Life.